O potrzebie wzmocnienia ochrony przedsiębiorców oraz innych podmiotów niebędących konsumentami przed nadużyciami wolności kontraktowej - Sołtys, Bogusław (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The study expresses the necessity to reinforce the legal protection for all the subjects using standard agreements in cases of freedom of contract abuse. During last decade, the emphasis of the legislator was focused only on the protection of consumers, what has paradoxically caused a significant degradation of other subjects’ protection, even though other subjects, as well as consumers, have no influence on formation of the standard agreements they enter. The situation develops numerous negative results not only in the individual but also in social and economic dimension. Moreover, in case of micro, small and middle-sized entrepreneurs it leads to collision of the reality with obligations nd declarations of the state to support these entrepreneurs.
Keywords: ochrona prawna; przedsiębiorcy; wolność kontraktowa; małe i średnie przedsiębiorstwa